2014
DOI: 10.1111/jfpp.12363
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of PVA/ZnO Nanocomposite

Abstract: ZnO nanoparticles were synthesized by the sol-gel method. The nanoparticles were added to polyvinyl alcohol (PVA) biopolymer to compare the microstructural, mechanical, antibacterial and physical properties of bionanocomposite films reinforced with various loading contents (1, 3 and 5 wt %) and thicknesses (70, 100 and 130 μm). Results showed that with increasing ZnO content to 3 wt %, the tensile strength and Young's modulus increased by 64 and 72%, respectively. The least amount of water vapor permeability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…The WVTR of the PVA films incorporated with different concentrations of GTE was given in Figure . The WVTR of pure PVA film was in the order of those previous researches reported for PVA films (Gharoy Ahangar, Abbaspour‐Fard, Shahtahmassebi, Khojastehpour, & Maddahi, ; Marcos, Aymerich, Monfort, & Garriga, ; Wang et al, ). The WVTR of PVA films was slightly reduced when GTE was added into the films, which was reduced from 1.87 (g·m −2 ·d −1 ) for PVA‐GTE 0% film to 1.03 (g·m −2 ·d −1 ) for PVA‐GTE 2% film.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The WVTR of the PVA films incorporated with different concentrations of GTE was given in Figure . The WVTR of pure PVA film was in the order of those previous researches reported for PVA films (Gharoy Ahangar, Abbaspour‐Fard, Shahtahmassebi, Khojastehpour, & Maddahi, ; Marcos, Aymerich, Monfort, & Garriga, ; Wang et al, ). The WVTR of PVA films was slightly reduced when GTE was added into the films, which was reduced from 1.87 (g·m −2 ·d −1 ) for PVA‐GTE 0% film to 1.03 (g·m −2 ·d −1 ) for PVA‐GTE 2% film.…”
Section: Resultssupporting
confidence: 78%
“…PVA is a humidity sensitive polymer and water molecules can be absorbed to interact with the polymer chains, which caused reduction of intermolecular interactions and increase of flexibility (Marcos et al, ), and as a consequence the water molecular diffusion through film was accelerated. It is well known that polyphenolic compounds contain many hydrophobic groups (Gharoy Ahangar et al, ), like benzene ring group, which improves hydrophobic property of the PVA film for incorporation of GTE. The water molecular diffusion was weakened as hydrophobic property of PVA films was improved.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO is a multifunctional nanoparticle approved by the Food and Drug Administration (FDA) and is used in several foods and cosmetics [ 30 ]. ZnO is also a very well-known nanofiller and has already been applied to fabricate numerous biopolymer-based films owing to its exceptional antimicrobial action, non-cytotoxicity, and high stability [ 31 , 32 , 33 ]. It has previously been shown that the incorporation of ZnO in biopolymers enhances their physical properties (mechanical and barrier) and provides the composite films with potent antimicrobial activities [ 30 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 16 ]. In addition, numerous studies have reported the preparation and the antibacterial efficacy of PVA films containing plant extracts, silver nanoparticles or zinc oxide nanoparticles [ 17 – 22 ]. However, when bacteria start to form biofilms they become resistant and conventional antibiotics do not eradicate biofilms from the surfaces where they formed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%